2012
DOI: 10.1016/j.febslet.2012.03.068
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐26 controls LXR‐dependent cholesterol efflux by targeting ABCA1 and ARL7

Abstract: Edited by Laszlo NagyKeywords: MicroRNA MiR-26 LXR Cholesterol efflux ABCA1 ARL7 a b s t r a c t Cellular cholesterol levels are tightly regulated and represent a balance of cholesterol uptake, endogenous synthesis and efflux. Although the classic transcriptional regulations of cholesterol metabolism by liver X receptors (LXRs) have been well studied, the potential effects of LXRresponsive microRNAs (miRNAs) still need to be unveiled. Here, we describe that miR-26, an LXR-suppressed miRNA, inhibits the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 44 publications
1
90
0
2
Order By: Relevance
“…57 It has been reported that the miR-26 family are involved in human adipogenesis. 49 , 22 More importantly, the miR-26a/b are expressed concomitantly with their host genes in GMEC. Our data revealed a functional significance between miR-26a/b and the CTDSP family in the regulation of lipid metabolism in GMEC, which is consistent with the effect on human adipogenesis 22 , 48 and in cell cycle control.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been reported that the miR-26 family are involved in human adipogenesis. 49 , 22 More importantly, the miR-26a/b are expressed concomitantly with their host genes in GMEC. Our data revealed a functional significance between miR-26a/b and the CTDSP family in the regulation of lipid metabolism in GMEC, which is consistent with the effect on human adipogenesis 22 , 48 and in cell cycle control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other miRNAs, including miR-33 (Rayner et al, 2011), miR-785 (Ramirez et al, 2011), miR-106b and miR-26 (Kim et al, 2012Sun et al, 2012), have also been shown to regulate the expression of ABCA1, and whether there are interactions between LXRs and these miRNAs remains to be determined.…”
Section: ! 53mentioning
confidence: 99%
“…70 Another aspect of the posttranscriptional regulation of ABCA1 comes from a recent report showing that the ATP-binding cassette transporter, ABCA12, increases ABCA1 stability and enhances macrophage cholesterol efflux in a liver X receptor-β-dependent manner.…”
mentioning
confidence: 99%